Therapy, Pain & Training - Treff G; Sareban M; Schmidt WFJ (Deutsche Zeitschrift für Sportmedizin)
Many endurance athletes aim to increase endurance performance at or near sea-level by hypoxic training, which can be realized in natural or artificial altitude via three main concepts: living and training in hypoxia, living in hypoxia and training in normoxia, or living in normoxia and training in hypoxia. The scientific evidence for these concepts is surprisingly unclear, although several ergogenic adaptations to hypoxic training are well described. Hematologic acclimatization through an increase in hemoglobin mass is often considered the most important factor. But hematologic acclimatization does not explain the performance increase found by some studies, indicating other mechanisms and confounders determine successful training adaptation. This clinical review briefly summarizes the current, conflicting knowledge, lists confounders potentially influencing the outcome, and provides some practical guidance to coaches and clinicians for monitoring and optimizing hypoxic training as far as covered by evidence.Key Words: Hypoxia, Endurance Performance, Wearables, Elite Athletes, Endurance Training, Hemoglobin, Erythropoiesis